2017
DOI: 10.1002/adem.201600863
|View full text |Cite
|
Sign up to set email alerts
|

Developing Breathable Double‐Layered Fibrous Membranes Equipped with Water Pulling Mechanism Toward Clothing with Enhanced Comfort

Abstract: Quick transfer of sweat from skin to atmosphere and dryness of textile inner surface are of scientific and commercial interests. However, creating a balance between these two parameters remains a serious challenge. In this work, electrospun double-layered membranes constructed of poly(vinylidene fluoride) fibrous layer (as inner hydrophobic layer) and nylon6 nanofibrous layer (as outer hydrophilic layer) are produced. Once a thin hydrophobic layer is considered, the enhanced water pulling mechanism is balanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…Compared with the AOTI value of DPP 2.5 /DCotton fibrous mat (spinning time of 2.5 hr), there is a decrease in DPP 3 / DCotton and certain quantity of water is retained in the top layer, ascribed to highly thick PP layer hindering water penetration. [30,31] 3.4 | Comprehensive analysis on directional moisture transport in fibrous mat Figure 7a visibly demonstrates the water transport progress in designed fibrous mat. It can be observed that when certain amount of droplets (200 μl) are dripped onto the surface of hydrophobic side, the droplets smoothly passes through the top layer rather than spread much on this side owning to its hydrophobic property, and only small ink stain appears on the surface.…”
Section: Effects Of Pp Layer Thickness On Directional Moisture Tranmentioning
confidence: 99%
“…Compared with the AOTI value of DPP 2.5 /DCotton fibrous mat (spinning time of 2.5 hr), there is a decrease in DPP 3 / DCotton and certain quantity of water is retained in the top layer, ascribed to highly thick PP layer hindering water penetration. [30,31] 3.4 | Comprehensive analysis on directional moisture transport in fibrous mat Figure 7a visibly demonstrates the water transport progress in designed fibrous mat. It can be observed that when certain amount of droplets (200 μl) are dripped onto the surface of hydrophobic side, the droplets smoothly passes through the top layer rather than spread much on this side owning to its hydrophobic property, and only small ink stain appears on the surface.…”
Section: Effects Of Pp Layer Thickness On Directional Moisture Tranmentioning
confidence: 99%
“…Conventional direction water transport fabrics are capable of transmitting body water and moisture mono‐directional, thus the perspiration is pulled away from the skin to the atmosphere rapidly. However, they are typically devoid of effective waterproofness in the inverse direction, resulting in poor protective function . Recently, W&B nanofibrous membranes have been successfully applied to solve this problem.…”
Section: Applications Of Electrospun Wandb Membranesmentioning
confidence: 99%
“…However, they are typically devoid of effective waterproofness in the inverse direction, resulting in poor protective function. [130] Recently, W&B nanofibrous membranes have been successfully applied to solve this problem. A typical example was given by the study of constructing trilayered W&B nanofibrous membranes with progressive wettability, transferring human sweat for quick evaporation and hindering outside liquid water penetration simultaneously.…”
Section: Functional Garmentsmentioning
confidence: 99%
“…Trilayered brous membranes 5 Continuous, spontaneous, and directional water transport Cellulose acetate-based nanobrous membranes 28 Breathable and colorful Nonwoven/Polyacrylonitrile-SiO 2 nanober composite membranes 10 Potential candidate for fast sweat release applications Double-layered membranes constructed of poly(vinylideneuoride) brous layer and nylon-6 nanobrous layer 33 Promising candidate for developing modern breathable textiles with enhanced moisture management properties such as sportswear Unidirectional water-penetration composite of hydrophobic polyurethane and hydrophilic crosslinked poly (vinyl alcohol) brous layers 1 An interesting "water diode" lm is fabricated via a facile electrospinning technique Dual-layer electrospun nanobrous mats consisting of polyacrylonitrile layer and polystyrene layer with and without interpenetrating nanopores, respectively 2 Tailoring surface hydrophilicity of porous electrospun nanobers to enhance capillary and push-pull effects for moisture wicking Presently, electrospun brous membranes can be prepared via solution electrospinning and melt-electrospinning. 11,12 The solution-electrospinning process is a method with ordinary operation, and bers can reach the nano-scale.…”
Section: Characteristicmentioning
confidence: 99%